2010
DOI: 10.1111/j.1600-0447.2009.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Mania associated with antidepressant treatment: comprehensive meta‐analytic review

Abstract: Use of ADs in adults with BPD or MDD was highly prevalent and moderately increased the risk of mania overall, with little protection by mood stabilizers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
188
3
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(217 citation statements)
references
References 101 publications
14
188
3
12
Order By: Relevance
“…These findings are of fundamental importance to guide clinical management of patients with comorbidity between BD and OCD and suggest that physicians might avoid treating comorbid OC symptoms in BD with antidepressants. In fact, such an approach might worsen BD via SRI-induced mania/hypomania (7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are of fundamental importance to guide clinical management of patients with comorbidity between BD and OCD and suggest that physicians might avoid treating comorbid OC symptoms in BD with antidepressants. In fact, such an approach might worsen BD via SRI-induced mania/hypomania (7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the comorbidity may represent a severe subtype of BD, or a severe subtype of OCD, or two separate disease entities that cooccur by chance. The clinical question is whether, and how, to treat the comorbidity because the main treatment for one disease (serotonin reuptake inhibitors, SRIs, for OCD) (5,6) can worsen the other (antidepressants, like SRIs, can cause mania and/or more mood episodes in BD) (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…According with the clinical observations that demonstrate the ineffectiveness of currently used mood stabilizers in preventing antidepressant-induced switch from depression to mania (Leverich et al, 2006;Tondo et al, 1981Tondo et al, , 2010 , lamotrigine (unpublished results) with imipramine fails to prevent the development of dopamine D2 receptor sensitization. Actually, carbamazepine seems to be effective, but its effect is due to the reduction of imipramine plasma levels due to the induction of the drug metabolism.…”
Section: Antidepressants Induce a "Bipolar-like Behaviour"mentioning
confidence: 99%
“…Indeed, Tondo et al [25] reported 12.5% of switch from depression to mania induced by antidepressants, and a great deal of evidence suggests that an increased dopaminergic transmission is associated with mania/hypomania [26][27][28][29][30].…”
mentioning
confidence: 99%
“…These findings indicated progressive and impressive improvement in the duration (from about 70% of total illness, 45% of depression, and 25% of mania/hypomania before memantine to less than 10% of total illness, 5% of depression, and 5% of mania hypomania after 3 years of memantine addition) and the severity of both affective phases of the disorder, with a greater improvement of depression than mania, and evidence of decreased severity of mania. Subjects with previous rapid-(≥ 4 episodes/year) or continuous-cycling were particularly improved.As for the possible mechanism of antimanic and mood stabilizing effect of memantine, we have demonstrated that chronic treatment with antidepressants sensitizes dopamine D2 receptors in the mesolimbic system, an effect that may contribute to their therapeutic action and may be responsible of their ability to induce switch from depression to mania in humans [11,12,[20][21][22][23][24].Indeed, Tondo et al [25] reported 12.5% of switch from depression to mania induced by antidepressants, and a great deal of evidence suggests that an increased dopaminergic transmission is associated with mania/hypomania [26][27][28][29][30].The sensitization of dopamine receptors (mania) is followed by a progressive desensitization of those receptors, associated with a depressivelike behavior assessed in the forced swimming test of depression [31][32][33].Thus, antidepressants induce a bipolar-like behavior, mimicking a cycle of the manic depressive illness (mania followed by depression).Memantine prevents the bipolar-like behavior in rats. Indeed it prevents both the sensitization of dopamine receptors (mania) induced by chronic treatment with imipramine, and the ensuing desensitization associated with the depressive behavior [33].…”
mentioning
confidence: 99%